2016
DOI: 10.3233/jbr-160127
|View full text |Cite
|
Sign up to set email alerts
|

Multi-radical (ORACMR5) antioxidant capacity of selected berries and effects of food processing

Abstract: Abstract. BACKGROUND:Fruits and berries are known to contain relatively high amounts of antioxidant/bioactive compounds. Several methods have been used for measurement of antioxidant capacity (AC), but not all methods have direct relevance to in vivo antioxidant status. OBJECTIVE: Determine AC in berry/fruit samples, processed berry products, and purified compounds by utilizing 5 different biologically relevant free radical/oxidant sources. METHODS: Samples were assayed for AC capacity using 5 different free r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 37 publications
(49 reference statements)
0
34
0
2
Order By: Relevance
“…The TAC (Prior, Sintara, & Chang, ) of the ethanol extract was measured using a T‐AOC assay kit (Nanjing Jiancheng Bioengineering Institute, China) according to the instructions of the kit (Wei, Wu, Chen, & Gu, ). The results were expressed in µmol of vitamin C equivalents per gram of the thawed peach samples (µM VCE/g).…”
Section: Methodsmentioning
confidence: 99%
“…The TAC (Prior, Sintara, & Chang, ) of the ethanol extract was measured using a T‐AOC assay kit (Nanjing Jiancheng Bioengineering Institute, China) according to the instructions of the kit (Wei, Wu, Chen, & Gu, ). The results were expressed in µmol of vitamin C equivalents per gram of the thawed peach samples (µM VCE/g).…”
Section: Methodsmentioning
confidence: 99%
“…No significant ( P > 0.05) correlation was observed among the ORAC values and the total content of ANCs, PPs and HAcs. Moreover, it has been reported that compounds from the flavan‐3‐ol and flavonol families presented higher ORAC activity than those from other phenolic families, such as anthocyanins and phenolic acids . Contrarily, these authors concluded that vitamin C did not present ORAC activity .…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, it has been reported that compounds from the flavan-3-ol and flavonol families presented higher ORAC activity than those from other phenolic families, such as anthocyanins and phenolic acids. 50,51 Contrarily, these authors concluded that vitamin C did not present ORAC activity. 50 In summary, it can be concluded that the ORAC activity of the assayed smoothies was mainly linked to the flavan-3-ols and flavonols.…”
Section: Antioxidant Capacity (Ac)mentioning
confidence: 98%
See 1 more Smart Citation
“…It is well known that lipids may be oxidised in vitro or in vivo by multiple oxidants, the products of which are key factors in conditions including atherosclerosis, neurological disorders, cancer and aging (3)(4)(5). Although oxidation may trigger a chain of chemical reactions and damage cells, certain antioxidants are able to terminate these chain reactions, exerting beneficial effects with regard to health maintenance and disease prevention (6)(7)(8). Oxidation due to exposure to oxygen and sunlight makes unsaturated fats turn rancid and become discoloured, and therefore, antioxidants are widely used as food additives to protect against degradation (9).…”
Section: Introductionmentioning
confidence: 99%